2008
DOI: 10.1002/jobm.200800002
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal diversity in acid mine drainage from Dabaoshan Mine, China

Abstract: Three acid mine drainage (AMD) samples collected from Dabaoshan Mine (Guangdong Province, China) were studied. In addition to physicochemical analyses, the diversity and community structures of the archaeal communities in these samples were described at the genetic level by amplified ribosomal DNA restriction analysis (ARDRA). Nine different ARDRA patterns were obtained from 146 clones and were studied as operational taxonomic units (OTUs), which were re-amplified and sequenced. Sequence data and phylogenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…Picrophilaceae and Thermoplasmataleslike phylotypes (but not Ferroplasma related) were detected which were related to sequences from an extremely acidic, metal-rich stream in Spain (65). This result is similar to those from other acid mine drainage sites where Thermoplasmatales represent a dominant group (3,20,22,62) but contrasts with the results for other sites where Ferroplasma spp. appear to be responsible for pyrite leaching (20,21).…”
Section: Discussioncontrasting
confidence: 45%
“…Picrophilaceae and Thermoplasmataleslike phylotypes (but not Ferroplasma related) were detected which were related to sequences from an extremely acidic, metal-rich stream in Spain (65). This result is similar to those from other acid mine drainage sites where Thermoplasmatales represent a dominant group (3,20,22,62) but contrasts with the results for other sites where Ferroplasma spp. appear to be responsible for pyrite leaching (20,21).…”
Section: Discussioncontrasting
confidence: 45%
“…AMD is a prevalent, international environmental problem that threatens aquatic life and surrounding ecosystems (11,15,21,24,26,33,43,44), although it also has been regarded as an excellent model to investigate linkages between microbial communities and geochemistry because of its relatively simple microbial community composition and structure (5,6,8). A better understanding of the microbial community diversity and ecology in AMD would provide a scientific foundation not only for the bioremediation of AMD-contaminated environments but also for potential applications for the energy-efficient recovery of valuable metals from mine waste and the removal of sulfur from coal (6, 23).The phylogenetic diversity of AMD microbial communities has been well studied by 16S rRNA-based approaches, including PCR cloning (36,54,55,57), denaturing gradient gel electrophoresis (DGGE) (10,20,21), fluorescence in situ hybridization (9,29,40), and oligonucleotide microarrays (14, 56). For instance, the DNA sequencing of a natural acidophilic biofilm (pH 0.80) revealed that pathways for carbon and nitrogen fixation and energy generation might occur in these communities and provided insight into survival strategies in such an extreme environment (45).…”
mentioning
confidence: 99%
“…The phylogenetic diversity of AMD microbial communities has been well studied by 16S rRNA-based approaches, including PCR cloning (36,54,55,57), denaturing gradient gel electrophoresis (DGGE) (10,20,21), fluorescence in situ hybridization (9,29,40), and oligonucleotide microarrays (14, 56). For instance, the DNA sequencing of a natural acidophilic biofilm (pH 0.80) revealed that pathways for carbon and nitrogen fixation and energy generation might occur in these communities and provided insight into survival strategies in such an extreme environment (45).…”
mentioning
confidence: 99%
“…Detection or quantification of the Ferroplasmaceae in these environments was done mostly using small subunit (SSU) rRNA-targeting analyses, such as 16S rRNA gene clone libraries' sequencing, amplified rRNA gene restriction analysis (ARDRA) profiling, real-time quantitative PCR, restriction fragment length polymorphism (RFLP) or fluorescence in situ hybridization (FISH), and oligonucleotide microarray analysis, all of which revealed the presence of these archaea in a number of pyritic/arsenopyritic, gold-arsenopyritic/chalcopyritic, and lead-, zinc-, and copper-containing mines across all continents (11,24,26,45,46,51,55,56,57,58). Clones related to the family Ferroplasmaceae have also been documented in further natural sulfide-rich ecosystems, e.g., in the snottites, i.e., the stalactite-like formations of microbial origin taken from the walls of Frasassi Cave and in the Rio Garrafo cave systems, both located in Italy, where acidic microenvironments were formed as a result of sulfide oxidation (38).…”
mentioning
confidence: 99%